Climate resilience platform and ACLIMATAR adaptation tools empower 400+ companies to build climate-resilient agricultural supply chains. - Talsma, Tiffany; Bunn, Christian; Schmidt, Paul G.; Castro Llanos, Fabio Alexander; Nguyen, Thuy Thanh; Nguyen, Nga Thanh; Basel, Ashleigh; Ha, Ly Nguyen; Perea, Carolay; Millar, Brendan; Craparo, Alessandro (2024)
The Alliance and partners developed the Climate Resilience Platform (CRP) and ACLIMATAR as complementary, free tools with a shared vision to equip agricultural supply chains with climate adaptation insights for improving cropping-system resilience. CRP has been selected by four key networks representing 400+ companies; and ACLIMATAR has been used by portfolio managers such as Rainforest Alliance for cocoa and coffee farm adaptation. CRP and ACLIMATAR amplify the wide dissemination of critical climate-resilience knowledge and tools, foster collaboration, and accelerate the adoption of climate-smart agricultural practices worldwide.